Mistake of Law as an Excuse - mehdi sabori pour (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2015)
One of the main factors affecting criminal culpability is mens rea and one important element of mens rea is knowledge of law. But this important factor is not exhaustively analyzed in the literature. Three kinds of ignorance of law have been analyzed in this article; one of them is direct mistake of law and two others are indirect mistake of law (or mistake of different law). Indirect mistake of law can be divided into two kinds: First, ignorance of different non-criminal law. In this kind of ignorance, perpetrator is not aware of a civil, tax, custom, marital or other kinds of non-criminal law. This kind of ignorance is an excusing factor. Second, ignorance of different criminal law. This kind of ignorance is not an excuse but can act as a mitigating factor. There is a third type of ignorance, which is exclusive to Iranian criminal law, which is about a canon law. None of these three kinds of ignorance have clear regulations in Islamic Penal Code and Legislature needs to enact related laws.